Toxicology of phosphorus, Fluorine and their inorganic compounds (protective role of food): monograph - Mamyrbayev, A. A. (б. и., 2015)
The book systematizes literature data and the results of in-house research in toxicology of inorganic phosphates and fluorides. It shows the modes of action of a yellow and red phosphorus, phosphine, hydrogen fluoride, and a number of other compounds of phosphorus and fluorine on protein metabolism, lipid metabolism, and carbohydrate metabolism, as well as bone metabolism. It examines the role and significance of individual nutrients in reduction of toxic effect of industrial poisons on a human body. The revealed disintegration of the lipid and protein components of biological membranes in the presence of an unbalanced diet is important for reducing desensitization of cell adenylate cyclase systems to catecholamines. It was found that under conditions of intoxication by inorganic compounds of phosphorus and fluorides there are significant disorders in the sympathoadrenal system and cyclic nucleotide metabolism The book is intended for toxicologists, biochemists. Bibliography - 352 references. Tables - 12